THEORITICAL REVIEW: TEORI MEREK HALAL - Yulfan Arif Nurohman (Among Makarti, 2018)
AbstractThe phenomenon of Islamic marketing and branding as a new and separate discipline has attracted the attention of both academics and practitioners. There is such confusion and improper use of the term of Islamic or Halal branding and until now there seems to be no clear understanding of what the term Halal branding means. For Muslims, branding cannot be separated from faith, which dictates that all actions should be divine and that one loves and hates not because of his humanly desires but because his feelings are in line with Allah’s guidance. Additionally, significantly in promoting and improving the Islamic brands to the consumers, producers or marketers need to follow all the requirements that required by authorization bodies either in organization’s practices and branding features to obtain consumer’s trust and confidence upon Islamic branding. The Halal market, i.e. products that are Shariah-compliant represents a significant portion of Indonesia’s economies. Developments in the growing field of Islamic marketing raise scholarly interest into its foundational principles and the many directions the field is taking. Keyword: halal, islamic brand, halal clusters, halal brand image